(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تهدف هذه الدراسة إلى إيجاد R مدى توزع أيونات B ,Al ,P, Asالمسرّعة بطاقات في المجال 50 – 300 keV المزروعة في هدف سيليكوني باستخدام طريقة شبه تجريبية لاشابته بحاملات شحنة من النوع n و p ثم حساب مقدار التشتت ∆Rp عن مسقط مسار الأيون Rp على امتداد الحزمة الأيونية الواردة, وذلك بافتراض أن وسيط التصادم يأخذ قيماً مختلفة من نصف قطر بور الذري. لقد تم حساب R باستخدام التكامل العددي وذلك بكتابة برنامج في Matlab . ولوحظ من الدراسة أن مدى توزع الأيونات المزروعة يزداد تدريجياً بزيادة طاقة الأيون المزروع وزيادة وسيط التصادم في المجال 0.053 – 0.795Å . This paper aims to calculate the distribution range R of implanted ions B ,Al ,P ,As in silicon target which accelerated to energies ranged between 50 – 300 keV using semi-empirical method in order to dope the Si –semiconductor with n and p type of charge carriers. In addition, we calculate the scattering parameter ( standard deviation) ∆Rp from the projected range Rp. For calculating R we used the numerical integration by writing a Matlab program in suggesting that the impact parameter p takes different values of Bohr radius. It is shown that the range distribution of implanted ions increases gradually by rising the ion beam energy and also by crowing the impact parameter in the interval 0.053 – 0.80Å.